2011
DOI: 10.1371/journal.ppat.1002169
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of TLR3 Signaling Due to Cleavage of TRIF by the Hepatitis A Virus Protease-Polymerase Processing Intermediate, 3CD

Abstract: Toll-like receptor 3 (TLR3) and cytosolic RIG-I-like helicases (RIG-I and MDA5) sense viral RNAs and activate innate immune signaling pathways that induce expression of interferon (IFN) through specific adaptor proteins, TIR domain-containing adaptor inducing interferon-β (TRIF), and mitochondrial antiviral signaling protein (MAVS), respectively. Previously, we demonstrated that hepatitis A virus (HAV), a unique hepatotropic human picornavirus, disrupts RIG-I/MDA5 signaling by targeting MAVS for cleavage by 3A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
111
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 43 publications
2
111
0
Order By: Relevance
“…Consistent with this, the TLR7-specific inhibitor, IRS-661, but not a control oligonucleotide, markedly blocked IFN-α production ( Figure 1D). We confirmed that pDCs were the responsible cell type by demonstrating a marked reduction in IFN-α production when peripheral mononuclear cells were depleted of BDCA4 + cells prior to cocultivation with infected cells type I IFNs (14)(15)(16)(17). Despite this, unlike the liver in acute hepatitis A, intrahepatic type I ISG expression is often robust in both acute and chronic hepatitis C (12,(18)(19)(20).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Consistent with this, the TLR7-specific inhibitor, IRS-661, but not a control oligonucleotide, markedly blocked IFN-α production ( Figure 1D). We confirmed that pDCs were the responsible cell type by demonstrating a marked reduction in IFN-α production when peripheral mononuclear cells were depleted of BDCA4 + cells prior to cocultivation with infected cells type I IFNs (14)(15)(16)(17). Despite this, unlike the liver in acute hepatitis A, intrahepatic type I ISG expression is often robust in both acute and chronic hepatitis C (12,(18)(19)(20).…”
Section: Introductionsupporting
confidence: 60%
“…It is interesting to note, however, that the viral RNA present within the activating eHAV particles was predominantly if not exclusively of genome length ( Figure 2D), consistent with it being entirely encapsidated. The lack of a strong type I ISG response within the liver during acute hepatitis A (12) can be attributed to the absence of pDCs within the liver during the peak phase of the infection coupled with the cleavage of both MAVS and TRIF by HAV proteases (14,15). The signals that result in the initial recruitment of pDCs to the liver early in the course of the infection ( Figure 4) are unknown.…”
Section: 4mentioning
confidence: 99%
“…S1A), the data presented here indicate that HAV must also possess potent mechanisms to disrupt IFN synthesis. This is supported by in vitro studies that show that HAV infection blocks the capacity of superinfecting viruses to induce type I IFN through the RIG-I/MDA5 pathway (36,37). We have shown that this is due to the HAV 3ABC protease, which is directed to the mitochondrial membrane where it cleaves MAVS (36).…”
Section: Discussionmentioning
confidence: 71%
“…We have shown that this is due to the HAV 3ABC protease, which is directed to the mitochondrial membrane where it cleaves MAVS (36). Recent data also indicate that the 3CD protease-polymerase processing intermediate disrupts TLR3 signaling by directing the cleavage of TRIF (37). HAV and HCV thus have evolved in a remarkably congruent fashion to target these signaling pathways and disrupt their ability to induce type I IFN synthesis.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, the 3CD protease-polymerase from hepatitis A virus was shown to disrupt TLR3-mediated activation of IRF3 and IFN-b promoter activation by targeting TRIF for degradation (48). Thus, it is clear that targeted degradation of TRIF, certainly by viruses, serves as a strategy to curtail antiviral immune signaling and as a more global mechanism to control inflammatory responses to pathogens.…”
Section: Discussionmentioning
confidence: 99%